Menciptakan Kesetaraan Gender - Israwati Israwati; Hanalir Hanalir (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
Gender equality is defined as a condition where women and men have equal conditions to be able to realize their full rights as human beings and to be able to contribute, and benefit from development. Therefore, gender equality is part of the development target for countries that experience high development such as Indonesia. This research aims to understand whether aggregateive democracy is incapable of meeting the demands of feminists? Feminists demand that women should be involved in life in the state. What do women want to participate? and what does their involvement look like? The results showed that women and men have differences, but that does not mean men and women do not have equality. The results showed that women and men have differences, but that does not mean men and women do not have equality. Democracy has opened up space to achieve that equality, but equality between men and women is difficult to achieve even in an aggregative democracy. To achieve that, participatory democracy is the solution, the reason is that women have basic needs that men never think about in making decisions in the legislature. To realize women's involvement, the concept of geunder-neutral and gender-differentiated citizenship can be a theory that can be implemented, one of which is through the adoption of a sequence number election system by placing women in the first sequence number.